A taxonomic review of the anilline genus Zeanillus Jeannel (Coleoptera: Carabidae: Bembidiini) of New Zealand, with descriptions of seven new species, re-classification of the species, and notes on their biogeography and evolution - Sokolov, Igor M. (Zootaxa, 2016)
Based upon external features of adults of the genus Zeanillus ten species are recognized, seven of which are new to science. Because of significant morphological differences, all species are arranged in four subgenera: the nominotypical subgenus Zeanillus, including Z. phyllobius (Broun), Z. punctigerus (Broun), and Z. nunni, new species (New Zealand, South Island, Otago, Trotters George); the monobasic subgenus Brounanillus, new subgenus, including Z. pallidus (Broun); the monobasic subgenus Nunnanillus, new subgenus, including Z. pellucidus, new species (New Zealand, South Island, Otago, Oamaru); and the most species-rich subgenus Otagonillus, new subgenus, including Z. brouni, new species (New Zealand, South Island, Otago, Oamaru), Z. lescheni, new species (New Zealand, South Island, Southland, Waikaia Forest), Z. carltoni, new species (New Zealand, South Island, Otago, Mount Watkin), Z. montivagus, new species (New Zealand, South Island, Otago, North Rough Ridge), and Z. nanus, new species (New Zealand, South Island, Otago, Waipori River Valley). Based on new morphological data, a redescription of genus, redescriptions of previously described species, and descriptions of all new taxa are given and a taxonomic key for all known species is provided. Maps of species distributions and illustrations of main taxonomic characters used in the text are also included. Some biogeographic/evolutionary aspects of Zeanillus origin and diversification are discussed.